Analisis Wacana Kritis Pemberitaan Harian Suara Merdeka, Harian Republika, Harian Kompas, dan Tabloid Derap Guru dalam Pembentukan Citra Guru - Dianastiti, Firstya Evi; Mardikantoro, Hari Bakti (Pascasarjana Universitas Negeri Semarang, 2016)
Dalam penelitian ini dibahas dimensi tekstual, praktik kewacanaan, dan dimensi sosiokultural pemberitaan di  Harian Suara Merdeka, Harian Republika, Harian Kompas, dan Tabloid Derap Guru dalam membentuk citra guru.  Pendekatan metodologis yang digunakan dalam penelitian ini adalah deskriptif kualitatif, sedangkan pendekatan teoretis Analisis Wacana Kritis (AWK) Norman Fairclough. Berdasarkan analisis data, diperoleh hasil sebagai berikut. Pertama, Wujud citra guru di Harian Suara Merdeka cenderung positif dengan persentase 66,67%. Harian Republika juga condong ke pembentukan citra positif dengan persentase 60%. Adapun Harian Kompas 100% condong ke citra negatif bagi guru. Sebaliknya, Tabloid Derap Guru 100% mengarah ke pembentukan citra positif.  Kedua, citra positif dan negatif tersebut ditentukan oleh praktik wacana yang terdapat di media massa yang bersangkutan. Ketiga, teks yang diproduksi media dipengaruhi oleh teks, praktik wacana, dan praktik sosiokultural.According to the study results, firstly, it was revealed how mass media constructed the image of teacher based on textual analysis through representation stage. Suara Merdeka daily news tended to shape positive image with the percentage of 66,67% compared to negative image of 33,33%. Republika daily news also had the same trend to shape positive image of teacher with the percentage of 60% and 40% of negative image. In addition, Kompas daily news had a tendency to shape a 100% negative image of teacher while Derap Guru tabloid had a 100% positive image. The percentage and the direction of the image of teacher was in accordance with the data collected from November 2015 to January 2016. Secondly, the analysis of the discourse practice was focused on production and consumption of text. Suara Merdeka, Republika, and Kompas daily news including Derap Guru Tabloid seemed to have certain considerations to select issues to be presented to the readers every day. Text production is closely linked to the ideology of the journalist and the enterprise. Derap Guru tabloid mostly wrote reports about teacher from PGRI view point. Meanwhile, SuaraMerdeka gave larger portion at various news about teacher. However, Republika and Kompas as a national daily news did not report teacher in detail. At the stage of text consumption, informants mostly delivered positive response to news about teacher at that daily news and tabloid. Thirdly, sociocultural practice dimension was analyzed on three levels; they are (1) situational, (2) institutional, (3) and social.